Step
*
1
of Lemma
prior-val-unique
1. Info : Type
2. es : EO+(Info)
3. T : Type
4. X : EClass(T)
5. e : E
6. ∀[e':E(X)]
     ({(↑e ∈b (X)') ∧ ((X)'(e) = X(e') ∈ T)}) supposing 
        ((∀e'':E. ((e' <loc e'') 
⇒ (e'' <loc e) 
⇒ (¬↑e'' ∈b X))) and 
        (e' <loc e))
7. e' : E(X)
8. (e' <loc e)
9. ¬(e' <loc prior(X)(e))
⊢ (X)'(e) = X(e') ∈ T
BY
{ ((InstHyp [⌈e'⌉] 6⋅ THEN Auto)
   THEN ParallelOp (-4)
   THEN (Assert e'' ≤loc prior(X)(e)  BY
               (BLemma `es-le-prior-interface-val` THEN Auto))
   THEN RelRST
   THEN Auto) }
1
1. Info : Type
2. es : EO+(Info)
3. T : Type
4. X : EClass(T)
5. e : E
6. ∀[e':E(X)]
     ({(↑e ∈b (X)') ∧ ((X)'(e) = X(e') ∈ T)}) supposing 
        ((∀e'':E. ((e' <loc e'') 
⇒ (e'' <loc e) 
⇒ (¬↑e'' ∈b X))) and 
        (e' <loc e))
7. e' : E(X)
8. (e' <loc e)
9. e'' : E@i
10. {(e' <loc e'')}@i
11. (e'' <loc e)@i
12. ↑e'' ∈b X@i
13. {e'' ≤loc prior(X)(e) }
14. (e' <loc e'')
⊢ prior(X)(e) ∈ E
Latex:
Latex:
1.  Info  :  Type
2.  es  :  EO+(Info)
3.  T  :  Type
4.  X  :  EClass(T)
5.  e  :  E
6.  \mforall{}[e':E(X)]
          (\{(\muparrow{}e  \mmember{}\msubb{}  (X)')  \mwedge{}  ((X)'(e)  =  X(e'))\})  supposing 
                ((\mforall{}e'':E.  ((e'  <loc  e'')  {}\mRightarrow{}  (e''  <loc  e)  {}\mRightarrow{}  (\mneg{}\muparrow{}e''  \mmember{}\msubb{}  X)))  and 
                (e'  <loc  e))
7.  e'  :  E(X)
8.  (e'  <loc  e)
9.  \mneg{}(e'  <loc  prior(X)(e))
\mvdash{}  (X)'(e)  =  X(e')
By
Latex:
((InstHyp  [\mkleeneopen{}e'\mkleeneclose{}]  6\mcdot{}  THEN  Auto)
  THEN  ParallelOp  (-4)
  THEN  (Assert  e''  \mleq{}loc  prior(X)(e)    BY
                          (BLemma  `es-le-prior-interface-val`  THEN  Auto))
  THEN  RelRST
  THEN  Auto)
Home
Index